Divalent metal transporter 1 (DMT1) in the brain: implications for a role in iron transport at the blood-brain barrier, and neuronal and glial pathology - Skjørringe, Tina; Burkhart, Annette; Johnsen, Kasper Bendix; Moos, Torben (Frontiers in Molecular Neuroscience, 2015)
Iron is required in a variety of essential processes in the body. In this review, we focus on iron transport in the brain and the role of the divalent metal transporter 1 (DMT1) vital for iron uptake in most cells. DMT1 locates to cellular membranes and endosomal membranes, where it is a key player in non-transferrin bound iron uptake and transferrin-bound iron uptake, respectively. Four isoforms of DMT1 exist, and their respective characteristics involve a complex cell-specific regulatory machinery all controlling iron transport across these membranes. This complexity reflects the fine balance required in iron homeostasis, as this metal is indispensable in many cell functions but highly toxic when appearing in excess. DMT1 expression in the brain is prominent in neurons. Of serious dispute is the expression of DMT1 in non-neuronal cells. Recent studies imply that DMT1 does exist in endosomes of brain capillary endothelial cells denoting the blood-brain barrier. This supports existing evidence that iron uptake at the BBB occurs by means of transferrin-receptor mediated endocytosis followed by detachment of iron from transferrin inside the acidic compartment of the endosome and DMT1-mediated pumping iron into the cytosol. The subsequent iron transport across the abluminal membrane into the brain likely occurs by ferroportin. The virtual absent expression of transferrin receptors and DMT1 in glial cells, i.e., astrocytes, microglia and oligodendrocytes, suggest that the steady state uptake of iron in glia is much lower than in neurons and/or other mechanisms for iron uptake in these cell types prevail.